Biogas from dedicated energy crops in Northern Italy: electric energy generation costs. Issue 4 (29th April 2014) - Schievano, Andrea; D'Imporzano, Giuliana; Orzi, Valentina; Colombo, Giorgio; Maggiore, Tommaso; Adani, Fabrizio
Abstract Agricultural anaerobic digestion facilities are increasing in many EU member States and biomass supply is sometimes an issue. Dedicated energy crops (DEC) (mainly Maize, Triticale and Sorghum) are often used to integrate other substrates, such as agricultural residues, manure and organic waste. However, DEC production includes onerous agricultural operations (soil preparation, harvest, transport and storage) and may result in high unit costs (UC) of electric energy (EE, € kWhe−1), compared to other renewable sources. In this work, seven different types of DEC (4 different combinations of crop successions) were cultivated in 30 different parcels, distributed along the Po Valley (northern Italy), using different varieties of seeds for each crop type. All agricultural operations were accounted for their costs (988–3346 € ha−1). Biomass production was measured and reported as average of different parcels for each type of crop (31.2–187 Mg ha−1). Biomass dry matter content and biogas potential were measured on representative samples and the EE obtainable was calculated (7.9–35.3 MWhe ha−1), by assuming conservative factors (CH4 contents in biogas and electric generation yields). The costs of ensiled biomass sensibly varied (13.8–40 € Mg−1) among crop solutions, as well as the same UC of EE (0.068–0.150 € kWhe−1). These costs were considered together with typical plant management and investment costs (plant size: 0.5–1 MWe): total UC of EE generation through anaerobic digestion (considering 100% DEC) varied in a relatively wide range (0.143–0.279 € kWhe−1). When the biomass mix is 'blended' with low‐cost residues or organic waste, this range could be lowered to 0.096–187 € kWhe−1. Only this strategy and strong efforts in reducing technological investment/management costs can candidate biogas‐based EE as a really competitive renewable alternative to traditional sources, in the next future.